2022
DOI: 10.3847/1538-4357/ac927a
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmic Telescope That Lenses the Sunburst Arc, PSZ1 G311.65–18.48: Strong Gravitational Lensing Model and Source Plane Analysis*

Abstract: We present a strong-lensing analysis of the cluster PSZ1 G311.65−18.48, based on Hubble Space Telescope imaging, archival VLT/MUSE spectroscopy, and Chandra X-ray data. This cool-core cluster (z = 0.443) lenses the brightest lensed galaxy known, dubbed the “Sunburst Arc” (z = 2.3703), a Lyman continuum (LyC) emitting galaxy multiply imaged 12 times. We identify in this field 14 additional strongly lensed galaxies to constrain a strong-lens model and report secure spectroscopic redshifts of four of them. We mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…Such magnification variation across a small angular scale 0 5 is not well-described by the large-scale cluster lens, and could be caused by a nearby invisible dark matter subhalo. While lens modeling predicts that image (9) and image (10) should have similar magnifications (Pignataro et al 2021;Sharon et al 2022), photometric measurements from Vanzella et al (2022b) also confirmed a significant flux ratio of 2, albeit lower than those found in this work. This might be a hint for spatial fine structures in the lens model near images (9) and (10).…”
Section: Magnification Ratio Between Images 10 Andcontrasting
confidence: 55%
See 3 more Smart Citations
“…Such magnification variation across a small angular scale 0 5 is not well-described by the large-scale cluster lens, and could be caused by a nearby invisible dark matter subhalo. While lens modeling predicts that image (9) and image (10) should have similar magnifications (Pignataro et al 2021;Sharon et al 2022), photometric measurements from Vanzella et al (2022b) also confirmed a significant flux ratio of 2, albeit lower than those found in this work. This might be a hint for spatial fine structures in the lens model near images (9) and (10).…”
Section: Magnification Ratio Between Images 10 Andcontrasting
confidence: 55%
“…While Vanzella et al (2022b) predicted μ r = 1.2-1.3, Diego et al (2022) presented two models with μ r = 1.4, and μ r = 2.1, respectively. The source-plane reconstruction results of Sharon et al (2022) imply μ r = 1.6-2. We use a high fiducial value μ r = 2.…”
Section: Nebula Sizementioning
confidence: 97%
See 2 more Smart Citations
“…Pioneering works in the pre-James Webb Space Telescope (JWST) era have already reported on the detection of tiny starforming regions at cosmological distances by combining Hubble Space Telescope (HST) imaging and gravitational lensing (e.g., Ellis et al 2001) that have only recently been recognized as globular cluster precursor (GCP) candidates (Vanzella et al 2017(Vanzella et al , 2019; see also Elmegreen et al 2021;Welch et al 2023), along with the use of deep Very Large Telescope (VLT) Multi Unit Spectroscopic Explorer (MUSE) spectroscopy performed on the Hubble Frontier Fields (e.g., Vanzella et al 2021) or exploiting superlensed arcs like the Sunburst (Rigby et al 2017;Rivera-Thorsen et al 2019;Sharon et al 2022;Vanzella et al 2022a).…”
Section: Introductionmentioning
confidence: 99%